Antifungal Activities of the Combination of Ulin Wood Liquid Smoke and Hiyung Cayenne Pepper Root Endophytic Fungi Against Colletothricum capsici - Witiyasti Imaningsih; Mariana Mariana; Ahmad Budi Junaedi; Rasyidah Rasyidah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Chili farming faces several constraints, one of which is the pathogenic fungus Colletotrichum capsici. To overcome it can be used indigenous endophytic fungus and lliquid smoke of Ulin (Eusideroxylon zwageri Teijsm. & Binn.) wood which has the potential as antimicrobial can be used. This research aimed to quantify and measure the effectiveness of an antimicrobial liquid smoke, endophytic filtrate, and the combination to suppress C. capsici growth. Subsequently, the research was conducted to apply the liquid smoke, endophytic fungi, and the two combinations of treatments on the growth of C. capsici. Thus, the results of this research showed that liquid smoke with a concentration of 0.085-1.75% can inhibit 3.56-62.17% in range. Meanwhile, the endophytic fungi filtrate, of 2% concentration can inhibit 91.69% C. capsici. Two of the combination liquid smoke in a concentration of 0.68%, 1.36% and the endophytic fungi filtrate in 2% have a demonstrated to inhibit the growth of C. capsici with the highest inhibition into 88.08%. Based on the analysis results, liquid smoke, endophytic fungi filtrate, and a combination of both showed significantly different inhibitory effects between treatments. This indicates that all those three treatments have antimicrobial potential.